Pengukuran Kinerja Keuangan Menggunakan Analisis Rasio: Studi Pada PT Bank Pembangunan Daerah Jawa Timur Tbk - Vandika Syach Ramadhani; Muhammad Imron; Candra Aprilia Kusumaningtyas (CV ODIS, 2026)
The purpose of this study is to measure the financial performance using ratio analysis on PT Bank Pembangunan Daerah Jawa Timur Tbk. The data used in this research is secondary data from the years 2019 to 2023. The data analysis technique employed in this study is ratio analysis, including liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The results of this study at PT Bank Pembangunan Daerah Jawa Timur Tbk during the period 2019 to 2023 show that the liquidity ratio analysis measured using the Current Ratio has a healthy performance, as well as the measurement using the quick ratio also has a healthy performance. Solvency ratio analysis measured using the debt to assets ratio has an unhealthy performance, while the measurement using the debt to equity ratio has a healthy performance. Activity ratio analysis measured using total assets turn over has an unhealthy performance, while measurement using fixed assets turn over has a healthy performance. Analysis of profitability ratios as measured using return on assets and return on equity shows healthy performance